Extranodal marginal zone B-cell lymphoma of Mucosa-Associated Lymphoid Tissue (MALT lymphoma) in ulcerative colitis - Tadashi Terada (The Saudi Journal of Gastroenterology, 2014)
Extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) occurring in inflammatory bowel diseases, including ulcerative colitis (UC) and Crohn′s disease, has been reported, although it is extremely rare. An 18-year-old man with a two-years history of UC underwent colon endoscopy, and was found to have active total UC ranging from anus to cecum. Six biopsies were obtained. The microscopic examinations showed severe infiltrations of atypical small lymphocytes. They showed hyperchromatic nuclei and increased nucleocytoplasmic ratio and scattered immunoblastic cells. Centrocyte-like atypical lymphocytes, monocytoid cells, and plasma cells were seen in some places. Vague germinal centers were present, and apparent lymphoepithelial lesions were seen. No crypt abscesses were seen, and there were few neutrophils. No apparent other findings of UC were seen. Immunohistochemically, the atypical lymphocytes were positive for vimentin, CD45, CD20, CD79α, CD138, κ-chain, λ-chain, and p53 and Ki-67 antigen (labeling index = 63%). They were also positive for CD45RO, CD3, and CD15, but these positive cells were very scant compared with CD20 and CD79α. They were negative for CD10, CD30, CD56, cytokeratin (CK) AE1/3, CK CAM5.2, CK34BE12, CK5, CK6, CK7, CK8, CK14, CK18, CK19, CK20, EMA, chromogranin, synaptophysin, NSE, S100 protein, CEA, CA19-9, p63, and HMB45. Without clinical information, the appearances are those of MALT lymphoma. However, with clinical information, making the diagnosis of MALT lymphoma was hesitated. It is only mentioned herein that atypical lymphocytic infiltrations indistinguishable from MALT lymphoma occurred in an 18-year-old male patient with a two-year history of UC.